LIST 1971 : an international registry of research and innovation - Wasserman, Paul; O'Connell, Jeane; Harper, Margaret; Johnson, Ronald (New York : Science Associates ; International, 1972)
This volume of the LIS list is an update to the 1971 list which examines and addresses the problem of how to invent and develop a mechahnism for gathering and disseminating timely information on significant work in progress in librarianship and information science.
includes bibliography index
asm; 12/04/19
Loans
Keywords: information disemination